2020
DOI: 10.3390/cancers12010252
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interleukin-34 in Cancer

Abstract: Cross-talk between cancer cells and the immune cells occurring in the tumor microenvironment is crucial in promoting signals that foster tumor growth and metastasis. Both cancer cells and immune cells secrete various interleukins (IL), which, either directly or indirectly, stimulate cancer-cell proliferation, survival, and diffusion, as well as contribute to sculpt the immune microenvironment, thereby amplifying tumorigenic stimuli. IL-34, a cytokine produced by a wide range of cells, has been initially involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 60 publications
3
25
0
Order By: Relevance
“…These findings confirm and expand on the data of previous studies showing that monocytes/macrophages are the main targets of IL-34 17 . Our data are also in line with studies documenting the expression of IL-34 receptors in TAMs in other settings 7 . Next, we showed that CD68/ HLA-DRII-positive cells expressed IL-34 in both TICs and LPMCs preparations, even though the fraction of IL-34-positive cells was significantly higher in cancer cancer 19,20 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings confirm and expand on the data of previous studies showing that monocytes/macrophages are the main targets of IL-34 17 . Our data are also in line with studies documenting the expression of IL-34 receptors in TAMs in other settings 7 . Next, we showed that CD68/ HLA-DRII-positive cells expressed IL-34 in both TICs and LPMCs preparations, even though the fraction of IL-34-positive cells was significantly higher in cancer cancer 19,20 .…”
Section: Discussionsupporting
confidence: 92%
“…In this context, we have recently shown that CRC cells synthesize IL-34, a factor that expands CRC cell 6 . Interestingly, both neoplastic cells and nontumoral cells infiltrating CRC tissue express IL-34 receptors raising the possibility that IL-34 can mediate the cross-talk between cancer cells and other cells during colon carcinogenesis process 7 . This study was undertaken to examine whether IL-34 regulates the function of TAMs, as these cells are known to facilitate CRC progression 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both cancer cells and immune cells can secrete various interleukins such as IL-34 (Franzè et al, 2020 ), which can increase the recruitment of M2 macrophages and promote the growth and metastasis of osteosarcoma (Ségaliny et al, 2015 ). There is increasing evidences that IL-34 promotes tumorigenesis through autocrine and paracrine mechanisms.…”
Section: Macrophage and Bone Remodeling-related Bone Diseasesmentioning
confidence: 99%
“…Lastly, in this Special Issue, the implication of IL-34 in cancer has been reviewed [ 10 ]. The Monteleone group has raised a great review about the multiple roles of IL-34 in various cancers.…”
Section: Special Issue “Interleukin In Cancer Pathogenesis and Trementioning
confidence: 99%